Dimensional analysis and cluster of transformational leadership on public and private organizations - Adi Indrayanto (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2017)
Purpose: The research aims to investigate and examine the dimension of transformational leadership on the private and public organization. Methodology: Total number of mailed questionnaires was 150, and the total number of returned questionnaires was 110, but there were only 100 complete questionnaires; thus, the response rate is 73.3%. Confirmatory and cluster is performed for data analysis purpose. Findings: The result shows that all transformational leadership dimensions are confirmed loading on the right places. The result provides an account in establishing a dimension of transformational leadership that will give more evidence of MLQ questionnaire can adopted on public and private organization. The result also showed that the private and public have differences on transformational leadership dimension that has more important. Keywords: transformational leadership, confirmatory analysis, cluster analysis, private organization, public organization.